TANGGUNG JAWAB MENJALANKAN PROTOKOL KESEHATAN DI TENGAH PANDEMI COVID-19 DITINJAU DARI PERSPEKTIF ETIKA KRISTEN - Tony Salurante; Riste Silaen; Yane Keluanan; Yosia Belo (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2021)
This article describes the various views of Christian ethicists about the concept of responsibility. The paper attempts to better understand the meaning of responsibility for Christians during the pandemic covid 19, particularly in carrying out health protocols. It is said that responsibility is relevant to human ethics, moral life, and actions revealed through His love. When the notion of responsibility is only associated with a mere duty ethic, it will be trapped in consequentialism. Responsibility in Christian ethics is the manifestation of good deeds based on the grace of faith. This is the essence of the Christian life. Responsibility in Christianity reflects loving God and neighbor, not just the right or wrong attitude, because this action does not affect the promise of salvation. From the theological perspective, responsibility is considered retrospective responsibility for past actions and the consequences before God.